Pirani Gauge Inficon BPG400 Sebagai Alat Ukur dan Analisis Tekanan Pompa Vakum Berbasis Logika Fuzzy - M. Syafei Gozali (Politeknik Negeri Batam, 2017)
Vacuum Drying Oven (VDO) is used in soft lens drying process by applying vacuum pressure to soft lens. The vacuum pressure is produced by vacuum pump. Because performance of vacuum pump has a big effect to drying process, so vacuum pump performance need to know to keep in optimum performance (vague). Existing measurement device can only measure vacuum pressure, thus vacuum pump performance is analyzed manually. To solve this problem, research is conducted to existing measurement of Pirani Gauge. Output from Pirani gauge is connected to computer via RS-232 communication to be processed using C# program and Fuzzy logic so measurement result of vacuum pressure and vacuum pump performance can be displayed on computer screen. Result of research is vacuum pressure measurement result and vacuum pump performance are displayed on computer screen and define the Fuzzy rule that suitable with vacuum pump performance reference that analyzed manually.